2021
DOI: 10.1002/jmv.27138
|View full text |Cite
|
Sign up to set email alerts
|

Late‐onset intrauterine growth restriction and HHV‐6 infection: A pilot study

Abstract: Late-onset Intrauterine growth restriction (IUGR) refers to impaired growth and development of the fetus, characterized by placental morphological abnormalities that affect the fetus's supply of nutrients. Human leukocyte antigen-G (HLA-G) is physiologically expressed during pregnancy, but decreased in normal placenta during the last weeks of gestation possibly inducing childbirth. Several viruses involved in congenital infection, such as herpesviruses, exploit HLA-G expression as an immune-escape mechanism. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 39 publications
(79 reference statements)
0
9
0
Order By: Relevance
“…[6][7][8][9] The high percentage of newborns (42%) with low weight in relation to their gestational age from women suffering from PR in the early weeks of gestation, should confirm indirectly the finding of Bortolotti et al 1,2 It is plausible that HHV-6 infection of the placental endothelial cells may block different angiogenetic properties by inducing HLA-G molecules expression in endothelial cells and make the endothelial cells themselves insensitive to different vasculogenetic factors. [1][2][3] The final outcome would be endothelial cell dysfunction, inhibition of angiogenesis and inadequate remodeling of the spiral arteries with a reduced flow of maternal blood to the fetoplacental unit resulting in placental insufficiency, IUGR, and pre-eclampsia. 11 Overall, HHV-6 transplacental infection occurs in 1%-2% of pregnancies and may play a role in 43% of cases of primary unexplained infertility.…”
Section: Pityriasis Rosea Human Herpesvirus 6 Infection and Pregnancymentioning
confidence: 61%
“…[6][7][8][9] The high percentage of newborns (42%) with low weight in relation to their gestational age from women suffering from PR in the early weeks of gestation, should confirm indirectly the finding of Bortolotti et al 1,2 It is plausible that HHV-6 infection of the placental endothelial cells may block different angiogenetic properties by inducing HLA-G molecules expression in endothelial cells and make the endothelial cells themselves insensitive to different vasculogenetic factors. [1][2][3] The final outcome would be endothelial cell dysfunction, inhibition of angiogenesis and inadequate remodeling of the spiral arteries with a reduced flow of maternal blood to the fetoplacental unit resulting in placental insufficiency, IUGR, and pre-eclampsia. 11 Overall, HHV-6 transplacental infection occurs in 1%-2% of pregnancies and may play a role in 43% of cases of primary unexplained infertility.…”
Section: Pityriasis Rosea Human Herpesvirus 6 Infection and Pregnancymentioning
confidence: 61%
“…Since we have previously shown that HLA-G molecules are modulated during SARS-CoV-2 infection in the intestinal villi during thromboembolic events [ [19] , [20] , [21] ], we evaluated HLA-G expression in placenta samples taking into consideration the implication of HLA-G molecules during viral infection in pregnancy [ 18 ].…”
Section: Resultsmentioning
confidence: 99%
“…HLA-G placenta expression during pregnancy is characterized by peculiar changes, with high levels of the molecules in the first trimester, which are reducing as they approach the birth, in order to promote the typical inflammatory environment needed to induce the delivery [ 17 ]. The presence of placental infections might affect HLA-G expression, leading to placental and fetal disorders, as recently reported for HHV-6 infection in association with IUGR condition [ 18 ].…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…As a result, pregnant women show greater susceptibility and worse clinical outcomes in response to bacterial and viral infections, such as Listeria monocytogenes and COVID19, compared to age-matched non-pregnant women (2)(3)(4)(5). Moreover, infections and dysregulation of the immune system during pregnancy are associated with adverse cardioobstetric outcomes such as gestational hypertension and preeclampsia, as well as other obstetric complications including preterm birth, intrauterine growth restriction, and stillbirth (2,(6)(7)(8)(9). Unmethylated cytosine-phosphodiester-guanine (CpG) motifs are potent triggers of host immune responses via stimulation of toll-like receptor 9 (TLR9), which is a pattern recognition receptor of the innate immune system (10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%